Reactive hydride composites for efficient hydrogen energy storage - Nwakwuo, C (2011)
Solid state chemical storage of hydrogen in metals offers promising advantages over compressed hydrogen gas and condensed liquid hydrogen, especially for mobile applications with respect to safety and energy efficiency. However, no single metal hydride simultaneously satisfies the essential performance criteria for onboard hydrogen storage namely, high gravimetric and/or volumetric energy density, fast kinetics and favorable thermodynamics. Recently, a breakthrough achievement was made by the development of reactive hydride composites in which two metal hydride systems (e.g. NaBH4 and MgH2) are mixed together resulting in better sorption properties than the individual pure systems. In this approach, the formation of MgB2 by exothermic reaction destabilizes the composite and consequently reduces the overall enthalpy and sorption temperature of the endothermic desorption reaction. In this work the thermodynamic and kinetic properties of reactions in 2NaH + MgB2 + 4H2 ↔ 2NaBH4 + MgH2 and 3NaH + MgB2 + 4H2 ↔ 2NaBH4 + NaMgH3 were established using multiple experimental techniques like volumetric measurements, ex-situ and in-situ X-ray diffraction, calorimetry, and especially electron microscopy. Under the applied experimental conditions of 50 bar hydrogen and 400 °C during the hydrogenation of 2NaH + MgB2 and 0.1 bar hydrogen and 450 °C during the dehydrogenation of 2NaBH4 + MgH2, both reactions were kinetically limited and proceeded in multisteps. The absorption reaction was partial, being restricted by the unexpected formation of NaMgH3 which limits the formation of NaBH4 while the desorption reaction was complete and limited by the growth of MgB2 through some intermediate complexes at the Mg/NaBH4 interface where the intermediate phase forms a barrier to diffusion. Conversely, in the 3NaH + MgB2 system, absorption in 100 bar hydrogen and 300 °C was complete but slow, while in the 2NaBH4 + NaMgH3 system, complete desorption was achieved in multisteps under 0.1 bar hydrogen and 450 °C. The formation of intermediate and stable complexes during these reactions poses a significant restraint to hydrogen sorption reactions. However, lower onset sorption temperatures have been established in these systems than in the pure compounds due to their simultaneous destabilization in the composite state. This study have demonstrated the complexity of desorption and absorption mechanisms in these composite systems and the difficulty of obtaining such reactions at low temperatures required for mobile applications. This understanding of the rate limiting reaction steps in reactive hydride composites provides the basis for further optimization of these materials for efficient hydrogen storage applications.